Anti-fatigue composite Rhinetine 48k gel type sports nutritious food and process thereof
By designing a core-shell structure and a self-microemulsifying gel matrix, combined with an ion-crosslinking locking layer and supercritical fluid extraction loading technology, the problems of component stability and delivery efficiency in sports nutrition foods have been solved, achieving efficient delivery and bioavailability of oil-soluble and water-soluble components.
Patent Information
- Application Number
- CN202511471200.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-15
- Publication Date
- 2025-12-16
AI Technical Summary
Existing sports nutrition foods suffer from problems such as poor stability when multiple active ingredients are combined, difficulty in efficiently delivering oil-soluble and water-soluble components, and low bioavailability of active ingredients.
The gel capsules feature a core-shell structure with a core containing a composite self-microemulsifying gel matrix and an outer shell made of a functional sustained-release gel. An ion-crosslinking locking layer is formed through in-situ reaction. Combined with supercritical fluid extraction loading technology and a combined drying process, the stability of the components and the delivery efficiency are improved.
It achieves efficient delivery of oil-soluble and water-soluble components, enhances the physical stability of the capsules and the bioavailability of active ingredients, and ensures targeted release and efficient absorption in the gastrointestinal tract.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of sports nutrition, in particular to an anti-fatigue composite echinatin 48k gel-type sports nutrition food and a process thereof. BACKGROUND
[0002] Sports nutrition food, as a kind of functional food aiming to enhance sports ability and promote physical recovery, its dosage form and formula are constantly developing. Gel capsules (soft capsules) become a common dosage form for carrying various nutritional ingredients due to their accurate dosage, high bioavailability and effective masking of unpleasant odors.
[0003] With the deepening of the understanding of nutritional science, developing a composite product with synergistic effect has become the current technical trend. However, it is a great technical challenge to stably integrate various active ingredients with different physical and chemical properties, such as oil-soluble ingredients (such as plant oil rich in Omega-3), water-soluble ingredients (such as vitamins and active peptides), and solid functional raw materials (such as Chinese herbal medicine powder or fermentation products) in a single gel capsule system. Simple physical mixing often leads to stratification and decreased stability of the system, and unexpected interactions between active ingredients may occur, thereby affecting the shelf life and final efficacy of the product.
[0004] In addition, the delivery efficiency of active ingredients is a key measure of product quality. For oil-soluble nutrients, their inherent hydrophobicity limits their dispersion and absorption in the gastrointestinal tract, resulting in unsatisfactory bioavailability. At the same time, many solid-phase functional ingredients derived from natural products often exhibit slow dissolution rate due to high crystallinity or poor wettability, which directly restricts the extent of their effective absorption by the human body.
[0005] Some protein or enzyme substances with important physiological activity (such as natto kinase and earthworm kinase) are extremely sensitive to acidic environment. Conventional gelatin capsules will quickly dissolve in the stomach acid environment to release the contents, resulting in a large amount of inactivation of these core functional ingredients before they reach their main absorption site (the intestine), and thus the expected health benefits are greatly reduced.
[0006] Finally, the physical stability of the product is also a long-standing difficulty in the preparation and storage of gel capsules. Complex core contents may react with the capsule shell, or cause excessive internal stress due to improper drying process, thereby causing quality problems such as capsule adhesion, deformation, and even content leakage, which seriously affect the shelf life of the product and consumer acceptance. SUMMARY
[0007] In view of the deficiencies of the prior art, the anti-fatigue composite rhytidin 48k gel type sports nutrition food and its process are provided, which solves the problems of poor stability of various active ingredients, difficulty in efficient delivery of oil-soluble and water-soluble components and low bioavailability of active ingredients in the prior art.
[0008] To achieve the above object, the first aspect of the present application provides an anti-fatigue composite rhytidin 48k gel type sports nutrition food. The structure of the food is a gel capsule with a core-shell structure, which comprises a core content and a shell skin.
[0009] The core content is a composite self-microemulsifying gel matrix, which comprises, by mass per particle, an oil phase component (flaxseed oil 550.0-600.0 mg, sea buckthorn fruit oil 2.0-5.0 mg), an emulsifier (phospholipid 20.0-40.0 mg), an aqueous phase component (water-soluble vitamin 0.8-1.2 mg, active natto powder 1.0-3.0 mg, active earthworm protein powder 1.0-3.0 mg), a gel skeleton precursor (pH-sensitive biopolymer 10.0-20.0 mg) and a functional solid phase (monascus loaded powder 100.0-120.0 mg).
[0010] The oil phase component, the aqueous phase component and the emulsifier in the core content are specifically matched, so that they can spontaneously form an oil-water microemulsion with a small particle size in the gastrointestinal environment, increase the specific surface area of the oil-soluble active ingredient, and thus improve the dissolution rate and absorption efficiency in the body.
[0011] The shell skin is a functional sustained-release gel, which comprises, by mass per particle, a gelling agent 200-250 mg, a plasticizer 100-140 mg, one or more exogenous functional powders 20-70 mg and a pharmaceutical grade calcium salt 2.0-10.0 mg.
[0012] In a preferred technical solution, an ionically cross-linked locking layer generated by in-situ reaction is also formed at the interface between the core content and the shell skin. The formation mechanism of the ionically cross-linked locking layer is as follows: The pH-sensitive biopolymer in the core content is alginate, and the pharmaceutical grade calcium salt in the shell skin dissociates calcium ions during preparation.
[0013] During encapsulation and molding, the calcium ions diffuse from the shell skin to the interface of the core content, and ionically cross-link with the alginate at the interface to generate a calcium alginate gel layer with a dense structure and water insolubility.
[0014] The ion cross-linking locking layer physically enhances the interface bonding strength of the core-shell structure, effectively prevents premature leakage of the core content, and realizes the regulation of the content release behavior.
[0015] In a preferred technical solution, the exogenous functional powder specifically comprises ganoderma-loaded powder and gastrodine powder.
[0016] The second aspect of the present application provides a preparation process of the anti-fatigue composite rhytidin 48k gel-type sports nutrition food.
[0017] The preparation process comprises the following steps: S1, preparing core content: homogenizing the oil phase components, water phase components, emulsifiers, pH-sensitive biopolymers, and functional solid phase raw materials by high shear homogenization to prepare a composite self-microemulsifying gel matrix.
[0018] In a preferred solution, before high shear homogenization, the water phase components containing water-soluble active ingredients are first subjected to high-frequency ultrasonic treatment to disperse the water-soluble powder into smaller particles in the liquid using the cavitation effect of ultrasonic waves, thereby obtaining a more uniform suspension system.
[0019] S2, preparing shell capsule liquid: mixing and heating the gelling agent, plasticizer, exogenous functional powder, and raw material as a source of divalent cations to prepare a uniform functional capsule gel.
[0020] S3, pill pressing and interface cross-linking: using soft capsule pill pressing technology, the core content prepared in step S1 is encapsulated with the functional capsule gel prepared in step S2.
[0021] During the physical extrusion and interface contact of encapsulation, the source of divalent cations in the shell capsule instantly reacts in situ with the pH-sensitive biopolymer in the core content, forming the aforementioned ion cross-linking locking layer.
[0022] S4, combined drying: drying the encapsulated gel capsules in multiple stages.
[0023] In a preferred solution, the preliminary drying stage adopts dehumidification and shaping drying to remove most of the water on the surface of the capsules in a gentle manner and fix their shape. The final drying stage adopts microwave vacuum drying and includes a periodic temperature variation annealing program.
[0024] The specific mechanism of the periodic temperature variation annealing program is to alternately perform a drying stage of microwave heating at a first higher temperature and an annealing stage of stopping microwave heating at a second lower temperature.
[0025] The higher temperature microwave heating stage is used for efficient removal of moisture; the lower temperature annealing stage allows sufficient time for moisture inside the capsule to migrate to the surface, while releasing internal stress generated by the polymer network during the rapid moisture loss process.
[0026] This periodic procedure can effectively avoid hardening and cracking of the capsule surface, ensure uniform drying of the product inside and outside, meet the moisture content standard and maintain the physical structure integrity.
[0027] In the preparation process of the present application, the functional solid phase and exogenous functional powder are achieved through a specific pretreatment process. The preparation process uses supercritical fluid extraction loading technology to load the active components in the raw materials onto the inert porous carrier in a highly dispersed state. The specific steps are as follows: The raw materials are placed in an extraction kettle, and supercritical carbon dioxide fluid is used for extraction (for example, at a pressure of 20-35 MPa and a temperature of 35-50℃). Subsequently, the loading fluid containing the active components is introduced into a loading kettle containing the inert porous carrier, and the solubility of the active components in the supercritical fluid is reduced by accurately controlling the pressure or temperature, so that the active components are precipitated from the fluid and deposited on the surface and inside the pores of the carrier in a highly dispersed amorphous or microcrystalline state.
[0028] The active ingredients of the loading powder prepared by this pretreatment process have a large specific surface area, which significantly improves their dissolution performance in an aqueous environment.
[0029] In a specific process parameter scheme: the homogenization treatment temperature of step S1 is 25-45℃; the mixed heating temperature of step S2 is 60-70℃; the final drying stage of step S4 is carried out under a vacuum degree of 1-50kPa, wherein the first higher temperature is 40-60℃ and the second lower temperature is 20-35℃.
[0030] The present application provides an anti-fatigue composite pectin 48k gel type sports nutrition food and its process. Has the following beneficial effects: 1、The present application successfully integrates oil-soluble, water-soluble and solid active ingredients into a single delivery system by designing a unique core-shell structure and combining a composite self-microemulsifying gel matrix. The self-microemulsifying design of the core utilizes the synergistic effect of the oil phase, emulsifier and water phase to spontaneously form a nanoscale microemulsion in the body environment, greatly increasing the specific surface area of oil-soluble ingredients (such as flaxseed oil) and significantly improving their bioavailability; at the same time, the functional solid phase (such as red yeast rice loading powder) is stably embedded in the gel matrix, avoiding direct contact with other components and ensuring its chemical stability.
[0031] 2、The present application forms an ion cross-linking locking layer at the core-shell interface through in-situ reaction. The compact structure of the calcium alginate gel layer physically enhances the bonding strength and sealing property of the core-shell interface, effectively preventing premature leakage of the core content during storage and transportation. More importantly, the locking layer remains stable in the acidic environment of the stomach, but gradually dissolves due to the property change of the pH-sensitive polymer in the weak alkaline environment of the intestinal tract, thereby achieving intestinal positioning release of the core active ingredients, avoiding the destruction of sensitive substances such as active natto powder and earthworm protein powder by gastric acid, and improving the targeted delivery efficiency.
[0032] 3、The preparation process of the present application adopts supercritical fluid extraction loading technology to pretreat functional powder, and through combined drying technology to dry the final product, which shows significant technical superiority. The supercritical fluid extraction loading process enables the active components in red yeast rice, ganoderma lucidum and other raw materials to be deposited on the inert carrier in a highly dispersed state, greatly improving their solubility and dissolution rate. The microwave vacuum drying process containing the variable temperature annealing program, through the alternating cycle of heating and relaxation stage, effectively releases the internal stress of the capsule caused by rapid water loss while ensuring high drying efficiency, and finally obtains high-quality gel capsule products with complete physical structure, uniform internal and external drying and stable quality. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present application will be described below in a clear and complete manner. Obviously, the described embodiments are only a part of the embodiments of the present application, not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present application.
[0034] Experimental materials: The main raw materials and reagents used in the following examples and comparative examples are as follows, and the reagents not specifically described are commercially available analytical pure or higher grade products.
[0035] Linseed oil: CAS No. 8001-26-1; Sea buckthorn fruit oil: CAS No. 90106-68-6; Soybean phospholipid: CAS No. 8002-43-5; L-ascorbic acid: CAS No. 50-81-7; Sodium alginate: CAS No. 9005-38-3; Microcrystalline cellulose: CAS No. 9004-34-6; Gelatin: CAS No. 9000-70-8; Glycerol: CAS No. 56-81-5; Calcium chloride dihydrate: CAS No. 10035-04-8; Carbon dioxide: CAS No. 124-38-9.
[0036] Example 1-3: Example 1: The present example provides a preparation process of an anti-fatigue composite acanthosis 48k gel type sports nutrition food, the steps are as follows: 1. Product formula (per single particle): Core content: flaxseed oil 580.0 mg, sea buckthorn fruit oil 3.0 mg, soybean phospholipid 30.0 mg, L-ascorbic acid 1.0 mg, active natto powder 2.0 mg, active earthworm protein powder 2.0 mg, sodium alginate 15.0 mg, and red yeast rice loaded powder 110.0 mg.
[0037] Shell capsule: gelatin 220.0 mg, glycerol 120.0 mg, lucid ganoderma loaded powder 30.0 mg, Gastrodia elata powder 20.0 mg, calcium chloride dihydrate 6.0 mg, and purified water in an appropriate amount.
[0038] 2. Preparation process: Pretreatment step, pretreatment of functional solid phase and exogenous functional powder: Prepare red yeast rice loaded powder and lucid ganoderma loaded powder. Mix the raw materials of red yeast rice powder or lucid ganoderma powder with microcrystalline cellulose at a mass ratio of 2:1 and place them in an extraction kettle.
[0039] Use supercritical carbon dioxide fluid for extraction, and the process parameters are controlled as follows: pressure 30 MPa, temperature 40℃.
[0040] Introduce the loaded fluid containing active components into a loading kettle containing inert porous carrier microcrystalline cellulose. By rapidly reducing the pressure, the active components are precipitated from the loaded fluid and deposited on the surface and pores of the microcrystalline cellulose, obtaining pretreated red yeast rice loaded powder and lucid ganoderma loaded powder for standby use.
[0041] Step S1, preparation of core content: Add L-ascorbic acid, active natto powder, and active earthworm protein powder to an appropriate amount of purified water, and use high-frequency ultrasonic treatment at a frequency of 40 kHz and a power of 300 W for 10 minutes to obtain a uniform aqueous suspension.
[0042] Subsequently, add flaxseed oil, sea buckthorn fruit oil, soybean phospholipid, sodium alginate, and red yeast rice loaded powder prepared in the pretreatment step to the above aqueous suspension. Use a high-shear homogenizer at a rotation speed of 8000 rpm for homogenization treatment at 35℃ for 20 minutes to prepare a composite self-microemulsifying gel matrix as the core content.
[0043] Step S2, preparation of the shell capsule skin liquid: Mix gelatin, glycerol, ganoderma lucidum loaded powder prepared in the pretreatment step, gastrodia elata powder, and calcium chloride dihydrate with appropriate amount of purified water in a gelatinization pot, heat to 65℃ and stir until all materials are completely dissolved to form a uniform functional capsule skin gel liquid.
[0044] Step S3, pill pressing and interface crosslinking: Use a soft capsule pill press to press the core content prepared in step S1 with the functional capsule skin gel liquid prepared in step S2. During the packaging process, calcium ions in the shell capsule skin and sodium alginate at the interface of the core content undergo in-situ ion crosslinking reaction.
[0045] Step S4, combined drying: After packaging, the gelatin capsule is preliminarily dried under the conditions of temperature 25℃, relative humidity 20%, and duration 6 hours.
[0046] After preliminary drying, the final drying is carried out in a microwave vacuum drying system. The system vacuum degree is maintained at 20kPa.
[0047] The drying program adopts a periodic temperature annealing program: first microwave heating at 50℃ for 10 minutes, then stop microwave heating at 30℃ for annealing for 5 minutes, and the program is cycled until the moisture content of the capsule reaches the predetermined standard to obtain the final product.
[0048] Example 2: This example provides another preparation process of an anti-fatigue composite spinoctin 48k gelatin type sports nutrition food: 1. Product formula (per single particle): Core content: flaxseed oil 550.0mg, sea buckthorn fruit oil 2.0mg, soybean phospholipid 20.0mg, L-ascorbic acid 0.8mg, active natto powder 1.0mg, active earthworm protein powder 1.0mg, sodium alginate 10.0mg, and red yeast rice loaded powder 100.0mg.
[0049] Shell capsule skin: gelatin 200.0mg, glycerol 100.0mg, ganoderma lucidum loaded powder 10.0mg, gastrodia elata powder 10.0mg, calcium chloride dihydrate 2.0mg, and appropriate amount of purified water.
[0050] 2. Preparation process: In the pretreatment step, the supercritical extraction process parameters are: pressure 20MPa, temperature 35℃.
[0051] In step S1, the temperature of high shear homogenization treatment is 25℃.
[0052] In step S2, the temperature of mixing and heating is 60℃.
[0053] In step S4, the final drying vacuum is 50 kPa, the first higher temperature of the periodic temperature change annealing procedure is 40°C, and the second lower temperature is 20°C.
[0054] The remaining process steps and conditions are the same as in Example 1.
[0055] Example 3: This example provides another preparation process for an anti-fatigue composite Spinosin 48k gel type sports nutritional food: 1. Product formula (per single particle): Core content: flaxseed oil 600.0 mg, sea buckthorn fruit oil 5.0 mg, soybean phospholipid 40.0 mg, L-ascorbic acid 1.2 mg, active natto powder 3.0 mg, active leech protein powder 3.0 mg, sodium alginate 20.0 mg, red yeast rice loaded powder 120.0 mg.
[0056] Shell capsule: gelatin 250.0 mg, glycerol 140.0 mg, ganoderma loaded powder 40.0 mg, Gastrodia elata powder 30.0 mg, calcium chloride dihydrate 10.0 mg, purified water q.s.
[0057] 2. Preparation process: In the pretreatment step, the supercritical extraction process parameters are: pressure 35 MPa, temperature 50°C.
[0058] In step S1, the high-shear homogenization temperature is 45°C.
[0059] In step S2, the temperature of the mixed heating is 70°C.
[0060] In step S4, the final drying vacuum is 1 kPa, the first higher temperature of the periodic temperature change annealing procedure is 60°C, and the second lower temperature is 35°C.
[0061] The remaining process steps and conditions are the same as in Example 1.
[0062] Comparative Examples 1-3: Comparative Example 1: Compared with Example 1, the difference is that in the preparation of the core content, no sodium alginate is added; at the same time, in the preparation of the shell capsule liquid, no calcium chloride dihydrate is added. The remaining raw materials and preparation process are the same as in Example 1.
[0063] Comparative Example 2: Compared with Example 1, the difference is that in the pretreatment step, no pretreatment is performed, and in steps S1 and S2, commercially available ordinary red yeast rice powder and ordinary ganoderma powder that have not been subjected to supercritical fluid extraction and loading treatment are directly used. The remaining raw materials and preparation process are the same as in Example 1.
[0064] Comparative Example 3: Compared with Example 1, the difference is that in Step S4, instead of using combined drying, the encapsulated gel capsules are continuously dried in a constant temperature blast drying oven at 50°C for 24 hours. The rest of the raw materials and preparation process are the same as Example 1.
[0065] Test Examples 1-3: Test Example 1, product stability test: 1. Experimental description: This test aims to evaluate the physical stability of gel capsules obtained by different preparation schemes under accelerated conditions.
[0066] Take the gel capsule samples prepared in Example 1, Comparative Example 1 and Comparative Example 3, and randomly select 100 capsules from each group. Place the samples in a clean petri dish, with the capsules laid flat in a single layer and not touching each other.
[0067] Place the open end of the petri dish containing the samples in a constant temperature and humidity chamber, and set the experimental conditions as follows: temperature 40±2°C, relative humidity 75±5%. At 10 days, 20 days and 30 days after the start of the experiment, take out the samples, and after equilibrating at room temperature for 30 minutes, observe and record.
[0068] The evaluation index is defined as follows: Appearance deformation rate (%): the percentage of the number of capsules that have undergone obvious softening, collapse, surface adhesion or capsule skin cracking to the total number of tests.
[0069] Content leakage rate (%): the percentage of the number of capsules with damaged capsule skin and oily contents overflowing onto the surface of the capsules or the bottom of the petri dish to the total number of tests.
[0070] 2. Experimental results: Table 1: Results of accelerated stability test
[0071] 3. Results analysis: From the experimental data in Table 1, it can be seen that during the 30-day accelerated stability test, the gel capsules prepared in Example 1 showed the lowest appearance deformation rate and content leakage rate. In contrast, the gel capsules prepared in Comparative Examples 1 and 3 had significantly higher appearance deformation rates and content leakage rates over time, indicating poor physical stability.
[0072] The sample of Example 1 has significantly improved stability compared to the sample of Comparative Example 1, which is due to the structural difference between them. In the preparation process of Example 1, the sodium alginate in the core content and the calcium ions in the shell capsule skin have an in-situ ion crosslinking reaction at the core-shell interface, forming a dense calcium alginate crosslinking layer.
[0073] The presence of this interface locking layer physically enhances the integrity and interface bonding strength of the core-shell structure, effectively inhibiting the movement of the core content and the impact on the capsule skin under temperature and humidity stress, thereby maintaining the structural integrity of the capsule and preventing the leakage of the content. The sample of Comparative Example 1 lacks this interface structure, and the bonding between the core and shell is only physical contact, so the bonding force is weak, and therefore the structure is more likely to fail.
[0074] The difference in stability exhibited by the sample of Example 1 compared to the sample of Comparative Example 3 is due to the difference in drying method in the preparation process. The combined drying process used in Example 1 includes a periodic temperature annealing program in the final drying stage.
[0075] Among them, the lower temperature annealing stage allows the internal stress generated in the capsule skin during the rapid water loss process to be periodically released and rearranged, resulting in a more uniform structure and lower stress in the capsule skin. The continuous constant temperature hot air drying used in Comparative Example 3 results in a large water gradient inside and outside the capsule skin, and the internal stress continues to accumulate, which is easy to form microcracks or defects in the capsule skin. These defects develop into macroscopic deformation and leakage under accelerated test conditions.
[0076] Test Example 2, in-vitro release behavior test: 1. Experimental description: This test aims to evaluate the in-vitro release behavior of gel capsules under different pH conditions simulating the gastrointestinal tract. The experiment uses the Chinese Pharmacopoeia method for determination of dissolution and release (second method, paddle method).
[0077] Take the gel capsule samples prepared in Example 1 and Comparative Example 1. Place a single particle capsule in a dissolution cup, and the dissolution medium is 900 mL of 0.1M hydrochloric acid solution (pH 1.2), the temperature is controlled at 37±0.5℃, and the rotation speed is 100 rpm. At 30, 60, 90, 120 minutes, take 5 mL of sample, and immediately supplement with an equal volume of fresh dissolution medium.
[0078] After the 120-minute sampling, phosphate buffer is added to the dissolution medium to accurately adjust the pH value of the medium to 6.8, simulating the intestinal environment, and the experiment continues. Continue to take samples at 150, 180, 240, 360 minutes.
[0079] After the samples were properly treated, the concentration of alpha-linolenic acid in each sample was determined by gas chromatography, and the cumulative release rate relative to the total content of the capsule was calculated.
[0080] 2. Experimental results: Table 2: In vitro cumulative release rate results
[0081] 3. Analysis of results: The data in Table 2 clearly shows the difference in release behavior of the two samples in different pH media.
[0082] The cumulative release rate of the core content of the sample prepared in Example 1 was less than 10% after 120 minutes of incubation in an acidic medium with pH 1.2. When the pH of the medium was adjusted to 6.8, the release rate significantly accelerated.
[0083] In contrast, the sample of Comparative Example 1 exhibited rapid and massive release in the acidic medium, with a cumulative release rate of more than 50% at 120 minutes.
[0084] The pH-dependent release characteristics exhibited by the sample of Example 1 are the result of the specific interfacial structure.
[0085] The calcium alginate cross-linked layer formed in situ at the core-shell interface of this sample is dense and insoluble under acidic conditions with pH 1.2, forming an effective physical barrier that retards the outward diffusion of the core content.
[0086] When the environment changes to neutral conditions with pH 6.8, the carboxyl groups on the alginate polymer chains deprotonate, the electrostatic repulsion increases, and ion exchange occurs, causing the cross-linked network structure to swell and disintegrate, and the barrier effect disappears, allowing the contents to be released rapidly.
[0087] The sample of Comparative Example 1 cannot form the above-mentioned interfacial cross-linked layer because sodium alginate and calcium ions are not introduced during preparation. Its outer shell capsule skin is a conventional gelatin matrix that begins to swell in aqueous media, and the release of the contents is mainly controlled by the hydration and dissolution rate of the capsule skin, and has no direct dependence on the environment pH.
[0088] Therefore, it occurs uncontrolled premature release in simulated gastric fluid. The results of this comparative experiment confirm that the in situ formed ionically cross-linked locking layer of is the technical basis for achieving the function of the product being stable in the simulated stomach environment and releasing in the simulated intestinal environment.
[0089] Test Example 3: In vitro dissolution rate test of functional ingredients: 1. Experimental description: This test aims to evaluate the effect of the pretreatment process of the functional solid phase on the in vitro dissolution rate of its active ingredients.
[0090] The red yeast powder prepared in Example 1 and the common red yeast powder used in Comparative Example 2 were taken as test samples respectively. The dissolution and release determination method (second method, paddle method) in Chinese Pharmacopoeia was adopted. Equal amount of lovastatin was contained in two powder samples which were accurately weighed and added into dissolution cups respectively. The dissolution medium was 900 mL of phosphate buffer (pH 6.8) and the temperature was controlled at 37 ± 0.5 °C with a rotation speed of 75 rpm. 5 mL of sample was taken at 5, 10, 20, 30, 45 and 60 minutes respectively and filtered through a 0.45 μm filter membrane.
[0091] The filtrate was determined for the concentration of lovastatin by high performance liquid chromatography (HPLC) and the cumulative dissolution percentage at different time points was calculated according to the initial feeding amount.
[0092] 2. Experimental results: Table 3: Cumulative dissolution results of red yeast powder in vitro
[0093] 3. Results analysis: The experimental data in Table 3 shows that the in vitro dissolution rate and the cumulative dissolution within 60 minutes of the active ingredient lovastatin of the red yeast powder used in Example 1 are significantly higher than those of the common red yeast powder used in Comparative Example 2. Within 30 minutes after the start of the experiment, the cumulative dissolution of the former is close to 90%, while that of the latter is only about 35%, and there is a significant difference between the two.
[0094] The fundamental reason for this difference in dissolution performance lies in the difference in the physical structure of the two powders, and this structural difference is determined by the preparation process.
[0095] In the preparation process of Example 1, the functional solid phase was pretreated by supercritical carbon dioxide fluid extraction. This process extracts the active component (lovastatin) from its original matrix and, by adjusting the pressure and temperature conditions, it is re-deposited on the surface and inside the pores of the inert porous carrier (microcrystalline cellulose) in a highly dispersed amorphous or microcrystalline state.
[0096] This highly dispersed solid form greatly increases the effective specific surface area of the active component in contact with the dissolution medium. According to the Noyes-Whitney dissolution theory, the dissolution rate is proportional to the specific surface area, so the increase in specific surface area directly leads to the increase in dissolution rate.
[0097] The ordinary red koji powder used in Comparative Example 2 still has its active ingredients in a natural, high-crystallinity state, and has a small specific surface area, resulting in a slow wetting and dissolution process in the dissolution medium. The comparative results confirm that the supercritical fluid loading pretreatment process is a key technical step for improving the dissolution performance of functional solid active ingredients.
[0098] While embodiments of the application have been shown and described, it is to be understood that the embodiments described are merely divergences of the principles and spirit of the application and that numerous modifications, changes, substitutions, and alterations can be made thereto without departing from the spirit and scope of the application as defined by the appended claims and their equivalents.
Claims
1. A fatigue-fatigue complex, 48k gel-type sports nutrition food, characterized in that, The food product is a core-shell structured gel capsule, comprising a core contents and an outer shell. The core contents are a composite self-microemulsifying gel matrix, comprising, by weight per capsule: Oil phase components: 550.0-600.0 mg linseed oil, 2.0-5.0 mg sea buckthorn fruit oil; Emulsifier: phospholipids 20.0-40.0 mg; Aqueous phase components: 0.8-1.2 mg of water-soluble vitamins, 1.0-3.0 mg of active natto powder, and 1.0-3.0 mg of active earthworm protein powder; Gel matrix precursor: pH-sensitive biopolymer 10.0-20.0 mg; Functional solid phase: Red yeast rice supported powder 100.0-120.0 mg; The outer capsule is a functional sustained-release gel, comprising, by weight per capsule: 200-250mg of gelling agent; Plasticizer 100-140mg; One or more exogenous functional powders, 20-70 mg; Pharmaceutical grade calcium salt 2.0-10.0mg.
2. The anti-fatigue compound strychnine 48k gel-type sports nutrition food according to claim 1, characterized in that, At the interface between the core contents and the outer shell, there is also an ion cross-linking locking layer formed by in-situ reaction; The pH-sensitive biopolymer is alginate, and the pharmaceutical-grade calcium salt dissociates in the outer shell to provide calcium ions as a divalent cation source. The ion crosslinking locking layer is a calcium alginate crosslinking layer generated by the reaction of the alginate with the calcium ions dissociated from the pharmaceutical-grade calcium salt.
3. The anti-fatigue compound strychnine 48k gel-type sports nutrition food according to claim 1, characterized in that, The exogenous functional powders include Ganoderma lucidum loaded powder and Gastrodia elata powder.
4. The preparation process of the anti-fatigue compound 48k gel-type sports nutrition food as described in any one of claims 1-3, characterized in that, Includes the following steps: S1. Preparation of core contents: Raw materials containing oil phase components, aqueous phase components, emulsifiers, pH-sensitive biopolymers and functional solid phases are homogenized by high shear to prepare a composite self-microemulsifying gel matrix. S2. Preparation of outer shell liquid: The raw materials containing gelling agent, plasticizer, exogenous functional powder and divalent cation source are mixed and heated to prepare a functional shell liquid. S3. Shot Capsulation and Interface Crosslinking: The core contents are encapsulated with the liquid of the functional capsule shell using a soft capsule shot-capsulation process. During the encapsulation process, the divalent cation source and the pH-sensitive biopolymer come into contact at the interface between the core contents and the outer capsule shell, forming an ion crosslinking locking layer in situ. S4. Combined drying: The packaged gel capsules are dried in multiple stages, including a preliminary drying stage and a final drying stage. The final drying stage uses microwave vacuum drying, and the microwave vacuum drying includes a periodic temperature-changing annealing process.
5. The preparation process of the anti-fatigue compound strychnine 48k gel-type sports nutrition food according to claim 4, characterized in that, In step S1, before performing the high-shear homogenization treatment, the aqueous phase component containing the water-soluble active ingredient is first subjected to high-frequency ultrasonic treatment.
6. The preparation process of the anti-fatigue compound strychnine 48k gel-type sports nutrition food according to claim 4, characterized in that, The preparation of the functional solid phase and exogenous functional powder mentioned in steps S1 and S2 is achieved through a pretreatment process, specifically including: The raw material, namely the functional solid phase or exogenous functional powder, is placed in an extraction vessel; The raw material was extracted using supercritical carbon dioxide fluid to obtain a loaded fluid containing active components; The loading fluid is introduced into a loading vessel containing an inert porous support. By adjusting the pressure or temperature conditions, the active component is precipitated from the loading fluid and deposited in a highly dispersed state on the surface and pores of the inert porous support, thereby obtaining the pretreated functional solid phase or exogenous functional powder.
7. The preparation process of the anti-fatigue compound strychnine 48k gel-type sports nutrition food according to claim 4, characterized in that, In step S4, the preliminary drying stage employs dehumidification and shaping drying.
8. The preparation process of the anti-fatigue compound strychnine 48k gel-type sports nutrition food according to claim 4, characterized in that, In step S4, the periodic variable-temperature annealing process includes: a drying stage in which microwave heating is performed at a first higher temperature, followed by an annealing stage in which microwave heating is stopped at a second lower temperature, and the drying stage and the annealing stage are performed cyclically.
9. The preparation process of the anti-fatigue compound strychnine 48k gel-type sports nutrition food according to claim 8, characterized in that, The specific process parameters for the preparation process are as follows: The high-shear homogenization process described in step S1 is carried out at 25-45°C; The temperature for mixing and heating in step S2 is 60-70℃; In step S4, the final drying stage is carried out under a vacuum of 1-50 kPa, and the first higher temperature in the periodic temperature-variable annealing process is 40-60°C, and the second lower temperature is 20-35°C.
10. The preparation process of the anti-fatigue compound strychnine 48k gel-type sports nutrition food according to claim 6, characterized in that, The process parameters for extracting the raw material using supercritical carbon dioxide fluid are: pressure 20-35 MPa, temperature 35-50℃.